Prinsip Pencegahan dalam Hubungannya dengan Prinsip Kebebasan Berlayar di Wilayah Selat - Nellyana Roesa; M. Putra Iqbal (Universitas Syiah Kuala, 2012)
ABSTRACT: International law of the sea has ruled that a coastal state and foreign ship have a right to and certain power in straits including Indonesia towards the Malaka Strait. It is one of the straits used as international shipping lane. UNCLOS 1982 admits that there is a transit passage right for foreign vessels shipping over the strait and it cannot be called by Indonesia as a coastal state directly faces the strait. In several matters, the passage is a border for the acknowledgement of Indonesia sovereignty over its territory. On the other side, international law provides the right for foreign vessels to have a passage without getting permission from Indonesia. However, a coastal state is also acknowledged its right to defend the sea from damage. The prevention principle is one of the reasons that can be justified by the state to maintain and protect the sea from damage caused by the using of the sea, by the passage right. International Law of the Sea Regarding Prevention Principle in Relation to the Freedom Principle of Sailing in Straits